074 Long-term effect of idebenone in reducing respiratory function decline in patients with Duchenne muscular dystrophy. Issue 6 (27th May 2022) - Servais, L; Mayer, OH; McDonald, CM; Voit, T; Mercuri, E; Buyse, GM
Abstract : Two placebo-controlled trials of 52-week duration showed that idebenone consistently reduced respira- tory function decline rate in patients with DMD. Long-term data from the DELPHI-Extension (DELPHI-E) study and SYROS (DELOS patients who transitioned to idebenone under an Expanded Access Program) are now presented. The aim was to assess the consistency of the long-term effect of idebenone. 11 DELPHI-E and 18 SYROS patients with abnormal (<80%) forced vital capacity (as percent predicted, FVC%p) were treated with idebenone for an average of 2.0 and 4.2 years respectively. Annualized FVC%p decline rates were compared to untreated patients from SYROS or matched external controls. Mean (SD) baseline age was 13.6 (2.3) and 13.3 (2.7) years in DELPHI (N=11) and DELOS (N=18), respec- tively, and FVC%p was 47.2% (19.7%) and 58.7% (17.6%). For the first 2-year period, the average annual decline rate was comparable in treated patients (4.5% and 5.4% in DELPHI-E and SYROS) and lower than in untreated SYROS patients and external controls (7.9% untreated and 8.1% in CINRG-DNHS). During years 3–6, the annual decline rate was consistently lower than for matched controls. Treatment with idebenone resulted in a sustained reduction in the rate of decline in respiratory function. laurent.servais@paediatrics.ox.ac.uk